Interactive Science Learning Innovation Management through the Design of Science Literacy-Based E-LKPD to Improve Conceptual Understanding - Sundari, Fitri Siti; Gani, Resyi A; Rahmah, Mursidah; Maulidia, Nur; Rizky, Keumala Septiyana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to develop a science literacy-based Electronic Student Worksheet (E-LKPD) to improve elementary students’ conceptual understanding of science, assess its feasibility, and evaluate its effectiveness. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the E-LKPD was developed with Canva and a live worksheet, focusing on the topic of force and motion. Expert validation showed high feasibility scores: 93% from the media expert, 95% from the language expert, and 94% from the material expert. A limited trial involving 30 fourth-grade students yielded positive responses: 92.42% from the students and 98% from the teachers. Pretest and posttest results showed an average N-Gain of 0.12 to 0.16, which falls within the low to moderate category. However, the Paired Sample T-Test produced p-values < 0.05 for all indicators, indicating statistically significant differences between pretest and posttest scores. This suggests that although the quantitative gain was modest, students’ conceptual understanding of science improved meaningfully. The findings indicate that the E-LKPD is highly feasible and effective for supporting science instruction. This research supports deeper conceptual learning, development of 21st-century skills, learning innovation, the Merdeka Curriculum, and teacher competency in integrating digital science-literacy tools.